Analysis of The Determinants of Layer Chicken Egg Supply in Tabanan Regency - Ni Luh Komang Ayu Herlina Sistadewi; I Gusti Agung Ayu Apsari Anandari (Harmony Management: International Journal of Management Science and Business, 2025)
This research is motivated by the dynamics of the layer chicken egg supply in Tabanan Regency. The purpose of this study is to analyze the factors that have the effect on the supply of layer chicken eggs, particularly the policy of banning the use of Antibiotic Growth Promoters (AGP), the number of layer chicken breeders, and the selling price of layer chicken eggs. The research method used is quantitative analysis with a multiple linear regression approach, using primary data obtained through questionnaires distributed to 101 layer chicken farmers in Tabanan Regency and analyzed with the assistance of EViews 12 software. The results show that the policy variable of banning the use of AGP has a negative and significant effect on the supply of layer chicken eggs. In contrast, the number of layer chicken breeders and the selling price of layer chicken eggs have a positive and significant effect on the supply. The coefficient of determination (R²) value of 0,316 indicates that the three independent variables are able to explain 31,6% of the variation in the supply of layer chicken eggs, while the remaining variation is affected by other factors outside the research model.